2007
DOI: 10.1152/ajprenal.00072.2007
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the pathophysiology of cyclosporine nephrotoxicity: a role of aldosterone

Abstract: Cyclosporine A (CsA), a calcineurin inhibitor, has improved allograft survival in solid organ transplantation and has been increasingly applied in the management of autoimmune diseases. While marked progress has been made in patient and allograft survival rates, clinical use of CsA is often limited by its nephrotoxic effect, which can be presented as two distinct and well-characterized forms: acute and chronic nephrotoxicity. The acute form is characterized by renal vasoconstriction, induced by an imbalance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(76 citation statements)
references
References 71 publications
(75 reference statements)
3
66
0
7
Order By: Relevance
“…Long-term exposure to CsA is associated with histologic damage to all compartments of the kidney [reviewed in (74 )]. TGF-␤-induced tubulointerstitial fibrosis is thought to be the primary mechanism driving progression of CsA nephropathy, which is characterized by loss of tubular epithelial cells and deposition of extracellular matrix in the tubulointerstitium (75 ). Another pathologic hallmark is arteriolar vasoconstriction, which leads to glomerular ischemia (76 ).…”
Section: Kidneymentioning
confidence: 99%
“…Long-term exposure to CsA is associated with histologic damage to all compartments of the kidney [reviewed in (74 )]. TGF-␤-induced tubulointerstitial fibrosis is thought to be the primary mechanism driving progression of CsA nephropathy, which is characterized by loss of tubular epithelial cells and deposition of extracellular matrix in the tubulointerstitium (75 ). Another pathologic hallmark is arteriolar vasoconstriction, which leads to glomerular ischemia (76 ).…”
Section: Kidneymentioning
confidence: 99%
“…The renoprotective effects of spironolactone or epleronone had been seen in many other animal models of renal injury not limited to diabetic nephropathy, as noted in a recent review by Nishiyama et al (46) These models included streptozotocin-induced and other forms of diabetic rats and mice, obese SHR rats, murine lupus nephritis, unilateral ureteral obstruction, ischemia reperfusion injury, 5/6 th nephrectomised rats and rats treated with AngII infusion, NO synthase inhibitor or cyclosporine (53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66). In these animal models, treatment with aldosterone blockers had no effect on systemic blood pressure.…”
Section: Aldosterone Biology and Lessons Learnt From Animal Modelsmentioning
confidence: 95%
“…In a single study, inhibition of RAS by ACE inhibitors has limited development of cyclosporine nephrotoxicity 124 and administration of angiotensin II blockers led to a significant reduction in plasma levels of TGF-β and endothelin 125,126 . In an experiment, application of spironolactone eliminated many of the RAS-and aldosterone-induced effects occurring during CI therapy 11 ; studies confirming these finding in humans are however not available.…”
Section: Alternative Optionsmentioning
confidence: 98%
“…It has been demonstrated that vasoconstriction is induced by activation of the renin-angiotensin system (RAS) and increase in levels of the vasoconstricting factors, endothelin and thromboxane, as well as suppression of synthesis of vasodilating prostacyclin, prostaglandin E2, and nitric oxide (NO) [9][10][11] . Interindividual susceptibility to cyclosporine-induced vasoconstriction also plays an important role 12 .…”
Section: Acute Arteriolopathymentioning
confidence: 99%